STUDY ON HOT CORROSION RESISTANCE AND MICROSTRUCTURE CHANGE OF AL0,75COCRFENI HIGH ENTROPY ALLOY IN NA2SO4 AND V2O5 MOLTEN SALT WITH ISOTHERMAL TEMPERATURE AT 1000 Â°C - William Pronodjojo, Joseph
Indonesia needs to increase the amount of power plant to fulfil its electical needs that is increasing each year. Superalloy is the main material for power plant turbine because of its good high temperature strength, but superalloy has a decrease in mechanical properties when it reaches 1200 °C. An alternative solution that can be considered is high entropy alloy Al0,75CoCrFeNi which is currently studied for its resistance of hot corrosion. In this research, the hot corrosion resistance of Al0,75CoCrFeNi in 50% Na2SO4 and 50% V2O5 molten salt mixture with isothermal temperature at 1000 °C. Experiment started with alloy melting using inert electric arc furnace into button, then homogenize it using horizontal furnace at 1100 °C for 10 hours. Homogenized sample cut into coupon. Hot corrosion experiment starts with rubbing salt paste composed of 50% Na2SO4 and 50% V2O5 to coupon and then put it into 1000 °C horizontal furnace for different isothermal time variation of 9, 16, 25, and 50 hours. After the experiment, samples will be characterized using optical microscope, x-ray diffraction (XRD), and scanning electron microscope (SEM). The results of the characterization are microstructure change, oxide composition, and elemental distribution. The experiment result shows that as-cast and as-homogenized sample have FCC and BCC phase. Homogenization affect BCC into A2/B2 and segregated. Oxides that are formed during hot corrosion experiment are Fe2O3, Fe3O4, Cr2O3, and NiO. There are also spinels formed as FeV2O4, CoFe2O4, CoCr2O4, Fe2NiO4, NiCr2O4, dan complex oxide FeCoCrO4. Hot corrosion mechanism starts at oxide forming of Al2O3, Cr2O3, Fe3O4, CoO, NiO, and Fe2O3. At the same time, sulphidation occur and react with Al and Cr forming Al2S3 and CrS. As temperature goes higher, Al2S3 is not stable, therefore only CrS remain. Sulphur can penetrate oxide layer through acid fluxing. Hot corrosion kinetic is logarithmic with coefficient value of 0,0065 g/cm2h.